Particle dynamics near extreme Kerr throat and supersymmetry; Journal of High Energy Physics; № 11 - Galajinsky A. V. Anton Vladimirovich (2010, 2010)
The extreme Kerr throat solution is believed to be non-supersymmetric. However, its isometry group SO(2, 1) × U(1) matches precisely the bosonic subgroup of N=2superconformal group in one dimension. In this paper we construct N=2supersymmetric extension of a massive particle moving near the horizon of the extreme Kerr black hole. Bosonic conserved charges are related to Killing vectors in a conventional way. Geometric interpretation of supersymmetry charges remains a challenge.